2020
DOI: 10.1186/s12875-020-01196-9
|View full text |Cite
|
Sign up to set email alerts
|

Understanding determinants of patients’ decisions to attend their family physician and to take antibiotics for upper respiratory tract infections: a qualitative descriptive study

Abstract: Background: Although antibiotics have little or no benefit for most upper respiratory tract infections (URTIs), they continue to be prescribed frequently in primary care. Physicians perceive that patients' expectations influence their antibiotic prescribing practice; however, not all patients seek antibiotic treatment despite having similar symptoms. In this study, we explored patients' views about URTIs, and the ways patients manage them (including attendance in primary care and taking antibiotics). Methods: … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…Our ethnographic study confirmed 'antibiotic beliefs' as influencing dentists too and identified it as a patient factor also. Interestingly, our study and another about antibiotics for upper respiratory tract infections [30] found that patients reported a good understanding the risks (and lack of benefits) of antibiotics, they still wanted them. The Wellcome Trust has also recognized the significance of patient beliefs about antibiotic risks and has recommended introducing a sense of personal jeopardy to messaging [31].…”
Section: Discussionmentioning
confidence: 68%
“…Our ethnographic study confirmed 'antibiotic beliefs' as influencing dentists too and identified it as a patient factor also. Interestingly, our study and another about antibiotics for upper respiratory tract infections [30] found that patients reported a good understanding the risks (and lack of benefits) of antibiotics, they still wanted them. The Wellcome Trust has also recognized the significance of patient beliefs about antibiotic risks and has recommended introducing a sense of personal jeopardy to messaging [31].…”
Section: Discussionmentioning
confidence: 68%
“…Also, the need for assessment, information, or reassurance rather than expectations for antibiotics, are possible reasons to consult (33)(34)(35). Most expect a thorough examination and explanation for their symptoms (36). Soliciting patient expectations could lead to higher patient satisfaction and reduced antibiotic prescribing (37)(38)(39).…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative research on this area has explored service users' [32] and prescribers' [33][34][35][36][37] attitudes towards delayed antibiotic prescription, prescribers' attitudes and experiences on antibiotic prescribing [38][39][40][41][42][43][44][45][46][47][48][49][50][51][52][53][54], service users' experiences on antibiotic use [38,39,48,51,[55][56][57][58], self-care treatments for ALRTIs [32,59], service users' [48,60] and health professionals' [47,48] understandings of AMR and antibiotic use, interactions between health Committee of the Institut de Recerca en Atenció Primària Jordi Gol i Gurina (IDIAPJGol) (contact via cei@idiapjgol.info) for researchers who meet the criteria for access to confidential data. For more information on data availability restrictions you can contact the ethics committee at cei@idiapjgol.info.…”
Section: Introductionmentioning
confidence: 99%
“…Recent qualitative research on this area has explored service users’ [ 32 ] and prescribers’ [ 33 37 ] attitudes towards delayed antibiotic prescription, prescribers’ attitudes and experiences on antibiotic prescribing [ 38 54 ], service users’ experiences on antibiotic use [ 38 , 39 , 48 , 51 , 55 58 ], self-care treatments for ALRTIs [ 32 , 59 ], service users’ [ 48 , 60 ] and health professionals’ [ 47 , 48 ] understandings of AMR and antibiotic use, interactions between health professionals and service users [ 47 ], experiences of ALRTIs [ 59 ], the role of pharmaceutical companies on antibiotic overprescribing and AMR [ 39 ], and socio-cultural factors to promote adequate antibiotic use [ 61 ]. These studies are mostly focused on health professionals’ experiences (rather than service users’) and take a conventional biomedical perspective to health and AMR.…”
Section: Introductionmentioning
confidence: 99%